1993
DOI: 10.1111/j.1526-4610.1993.hed3309497.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnoses and Symptom Patterns in Children Presenting to a Pediatric Headache Clinic

Abstract: The diagnosis of migraine headache in children and adolescents is complex and not well understood. This study was conducted to compare diagnostic rates, using various criteria for pediatric migraine, and specific symptom characteristics in a sample of children referred for care to a specialized pediatric headache clinic. A structured interview was used at the patient's initial assessment visit to elicit symptom patterns and therapies attempted for headache. Clinical diagnoses were based on consensus agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
87
1
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 0 publications
8
87
1
6
Order By: Relevance
“…The majority of children in the study had bilateral headaches which would be in keeping with many of the previous studies of children (Congdon and Forsythe 1979, Barlow 1984, Gladstein et al 1993, Seshia et al 1994. Rossi et al (1992) reported that 50% of the study population complained of the throbbing quafity of their headaches.…”
Section: Discussionsupporting
confidence: 68%
“…The majority of children in the study had bilateral headaches which would be in keeping with many of the previous studies of children (Congdon and Forsythe 1979, Barlow 1984, Gladstein et al 1993, Seshia et al 1994. Rossi et al (1992) reported that 50% of the study population complained of the throbbing quafity of their headaches.…”
Section: Discussionsupporting
confidence: 68%
“…Esta variabilidade tem sido encontrada em outras avaliações de pacientes pediátricos 4,5,12,13 , determinando propostas que alteram os critérios conhecidos -principalmente o da enxaqueca sem aura da IHS, visando torná-lo mais específico a esta faixa etária.…”
Section: Discussionunclassified
“…Tanto isto é verdade que a IHS acrescentou, em seu critério, um adendo diminuíndo de 4 para 2 horas o tempo mínimo exigido para o diagnóstico da enxaqueca sem aura, na infância. Contudo, alguns estudiosos 2,[4][5][6][7]12 afirmam que as crianças, na sua maioria, ainda têm crises menos prolongadas e que o período de uma hora ou menos seria suficiente para a determinação diagnóstica. Considerando, no grupo estudado por nós, os 36 casos classificados como enxaqueca sem aura pelo critério da IHS -associados ou não aos demais critérios -verificamos que 15 pacientes tinham crises que duravam menos do que 2 horas, 5 sofriam de crises que variavam de 2 a 4 horas, e 16 apresentavam crises de mais de 4 horas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Since 1992, many papers have shown the high specificity but low sensitivity of ICHD-I diagnostic criteria for migraine without aura in childhood [3][4][5][6][7][8][9][10][11][12][13][14][15]. Several published series have shown that the percentage of children in which the attack duration is less than 2 hours ranged from 11% to 32% [3,5,7,8,11].…”
Section: Discussionmentioning
confidence: 99%